Lingüística como padrão de escrita missionária - Barros, Maria Cândida Drumond Mendes (Cadernos de Linguagem e Sociedade, 2010)
This paper presents the history of two models of orthography for unwritten languages created by evangelical missions, using linguistic concepts. Their diffusion will be analysed as well as the linguistic concepts adopted for the notion of letter and the alliances established between scholars and missionaries in the formulation of these models.